Effect of implantation of nitrogen ions into VO2 thin films - Kumar, Manish; Singh, Saurabh; Lim, Weon Cheol; Chae, Keun Hwa; Lee, Hyun Hwi (Elsevier BV, 2022)
Modifications in the structural and electronic properties of VO2 films induced by N+ ion implantation were investigated. VO2 films prepared by radio frequency (RF) magnetron sputtering deposition on quartz substrate were subjected to the N+ ion beam with 55 keV at different fluences (1 x 10(15) and 1 x 10(16) ions/cm(2)). Compared with the pristine VO2 film (Tc similar to 342 K), structural and electrical phase transition temperatures were shifted around room temperature in the N+ ion implanted sample (fluence = 1 x 10(15) ions/cm(2)). Furthermore, a higher fluence of N+ ions (fluence = 1 x 10(16) ions/cm(2)) had significantly modified the crystalline structure of VO2 thin film, and a metallic behaviour was clearly noticed in the entire temperature range between 240 K and 373 K under this study. N+ ion implantation effectively induces the changes in the electronic structure of VO2 thin films, which are further confirmed by the X-ray absorption spectroscopy (XAS) measurements.